The Influence of Society's Cultural Aspects on Mosques' Architectural Symbolism-The Mosques Built Between “1970-1990” in Erbil city as Case study - Ali, Amjed M.; Qadir, Vian Sabr (Sulaimani Journal for Engineering Sciences, 2015)
There are spiritual and physical symbolic values of the mosques architecture. From the birth of Islam mosque architecture appeared in a simple form but with a spiritual symbolic value, then the mosque architecture developed as Islam spread in various regions and some new elements have been added for the functional needs and numerous styles of mosques appeared as a result in the diversity of identity and culture of each region. The research discusses that symbolism is one of the cultural aspects as it is one of the humane needs which rectifies society’s identity. On the other hand the evolution of mosque architecture mentions that new elements were added for utilitarian need and lasted a period which became symbols for the mosque buildings as well, then it sheds light on the interpretation of mosque architecture with other regions that resulted in various styles of mosque architecture. Therefore, the symbolism of mosque architecture could be obtained through two points one from its key symbolic elements and the other from its relation with local architecture. Thus, the research started to search and seeks to find the reasons for lacking a known local style of mosques in Erbil city, and the lack of symbolism in them. They even have been built in such a way that contrasted with some of the Islamic regulations. The research takes the factor of "cultural aspects" as an effective factor on appearing these kinds of mosques. The research concludes that removing some elements in the mosque building which most of them has a desirable symbolic value and besides that neglecting local architecture in the design of mosques led to lose symbolism in the mosque buildings in Erbil city. Thus, a large ratio of the architects could not recognize the mosque buildings as compared to some other buildings. The thesis sheds light on the cultural background of the society (governmental parties, architects, clients, etc.) that have a distinct effect on the symbolism ratio of the mosque buildings, unlike the project cost has a little bit influence, as most of the mosques which were built by the governmental parties have low symbolic value in spite of not having problems in the cost budget. The thesis concludes another important point which is the characteristics of the site (orientation, area and number of elevations) have a positive relation with the symbolism ratio of mosque, so the research recommends governmental parties and architects to take these points into consideration in the design of mosque buildings.